Telemetricky system pro diagnostiku casovych parametru chuze - Salinger, J.; Novotny, J.; Vychodil, R. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2000)
The authors present a hardware and software model of telemetric diagnostic system aimed at the measurement and evaluation of the time parameters of gait. The system comprises a sensor unit formed by specially adapted shoes, a radio transmitter and a receiver connected to a microcomputer via serial port COM 1 (2). Basic software equipment involves testing of sensors, measuring, calculation of time, spectral and statistic parameters. The system has been designed to monitor the load in the lower extremities during the course of various physical activities, for the purposes of evaluation of results of therapeutic rehabilitation, etc.